Evaluation of Performance of Rajasri Birds under Different Management Situations - Preetam, V. Chinni; Gurram, Srinivas; Qudratullah, S. (Indian Journal of Animal Nutrition, 2019)
A study was conducted to evaluate the performance and physical & chemical composition of crop contents of Rajasri bird reared under different systems. The control group was reared under intensive system offering ad lib. feed, while second and third groups were maintained under semi intensive system providing 20 and 40 percent of ad lib. feed respectively. The remaining two treatment groups were reared under scavenging, one group at farm (SC-F) and the other at farmer’s backyard (SC). Significantly (P